Pengaruh Pemberian Air Rebusan Daun Kelor terhadap Kadar Glukosa Darah pada Penderita Diabetes Melitus di Kelurahan Padaleu Kecamatan Kambu, Kendari - Ma’rifat Istiqa Mukty; Nina Isywara Kusuma; Andi Ade Ulasaswini; Nurhidayah Tiasya Sanas (Jurnal Sains dan Kesehatan, 2026)
Diabetes mellitus is a chronic metabolic disease characterized by elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. Uncontrolled diabetes can lead to various complications and decreased quality of life. Moringa oleifera leaves contain bioactive compounds, including flavonoids, vitamins A, C, and E, as well as selenium, which possess antioxidant properties and are believed to help reduce blood glucose levels. This study aims to determine the effect of Moringa leaf decoction on reducing blood glucose levels in patients with diabetes mellitus in Padaleu Village, Kambu District, Kendari City. The study employs a quantitative pre-experimental design using a one-group pretest-posttest approach. The population consists of 35 diabetes mellitus patients, with 17 respondents selected through purposive sampling. Blood glucose levels are measured before and after the administration of Moringa leaf decoction using a glucometer and observation sheets. Respondents receive 200 ml of Moringa leaf decoction daily for five consecutive days. Data analysis is conducted using paired statistical tests to determine differences in blood glucose levels before and after the intervention. The findings of this study are expected to provide scientific evidence regarding the effectiveness of Moringa leaf decoction as a non-pharmacological therapy for controlling blood glucose levels among diabetes mellitus patients. Furthermore, the results may contribute to nursing science development and serve as a reference for healthcare providers and future researchers in implementing complementary therapies for diabetes management.